VARIASI PENGGUNAAN KONJUNGSI SUBORDINATIF PADA RUBRIK SOSOK HARIAN KOMPAS - Lala Kartika Sandra; Dini Restiyanti Pratiwi (Jurnal Genre (Bahasa, Sastra, dan Pembelajarannya), 2021)
Conjunction is a conjunction that functions to connect or string words with words, clauses with clauses, sentences with sentences, paragraphs with paragraphs, and so on. Judging from the position of the constituents connected, conjunctions are divided into two, namely coordinating conjunctions and subordinating conjunctions. Subordinating conjunctions are conjunctions that connect two language units unequally. Kompas Daily is the name of an Indonesian newspaper headquartered in Jakarta. In the daily Kompas, there is one rubric, namely the Figure rubric. The Figure Rubric contains a person's life story both in Indonesia and abroad that can inspire and be imitated by readers. The objectives of this study is to describe the form of subordinating conjunctions in the Kompas daily figure rubric. The results in this study are based on Identification obtained 139 data containing subordinating conjunctions. Based on the classification of data, there are 7 types of subordinate conjunctions including: (a) because 43 data were found, (b) conditions were found 5 data, (c) purpose was found 21 data, (d) timing, 29 data was found, (e) presentation was found 15 data, (f) comparison found 7 data, and (g) the final limit found 19 data.Â